Study of Corrosion Penetration Rate on Composite Materials EN AC-43100 (AlSi10Mg (b)) + SiC* - Tjahjanti, Prantasi Harmi; Darminto, Darminto; Nugroho, Wibowo Harso; Ganda, Andita N.F. (International Journal of Integrated Engineering, 2019)
Corrosion Penetration Rate (CPR) is defined in three ways: (1) the speed at which any metal in a specific environment deteriorates due to a chemical reaction in the metal when it is exposed to a corrosive environment, (2) the amount of corrosion lossed per year in thickness, (3) the speed at which corrosion spreads to the inner portions of a material. The purpose of this research is calculations CPR of Aluminum matrix composite materials (AlSi10Mg (b)) with Silicon carbide (SiC*) reinforcement. A wet corrosion test was conducted  where  the AlSi10Mg(b) and AlSi10Mg(b)+SiC* were dipped in a solution of HCl acid, NaOH, NaCl and in pH solution 1,3,5,7,9,11, and 13.  It was found that the highest corrosion penetration rate occured when the specimen  dipped on  HCl solution and in pH 1 It was also found that the   addition of SiC* can reduce rate of corrosion in materials. Finally, this study showed that  composite material,  AC-43100 (AlSi10Mg (b)) 85% + 15% SiC*, was the best material in resist of corrosion attack, has smallest CPR below the standard corrosion